Seasonal malaria chemoprevention in northern Mozambique: a cost-effectiveness analysis - Neide Canana; Ivan Alejandro Pulido Tarquino; Sónia Enosse; Kevin Baker; Maria Rodrigues; Christian Rassi; Akashdeep Singh Chauhan; Chuks Nnaji; Baltazar Candrinho; Elisa M. Maffioli (Malaria Journal)
Abstract Background Malaria is endemic in Mozambique and one of the leading causes of death in children under 5 years old. In 2020 the country adopted the WHO-recommended seasonal malaria chemoprevention (SMC) strategy and delivered the intervention in all 23 districts of Nampula province between January and April 2023. The aim of this study is to estimate the cost-effectiveness of SMC in Nampula, Mozambique. Methods Financial cost of implementing SMC were estimated from a limited health care provider perspective for the year 2023 in US$. Data on resource use of the SMC implementation was assessed from Malaria Consortium records. The number of eligible and treated children was collected from surveys after cycle 4. The number of malaria cases, deaths and Disability Adjusted Life-Years (DALYs) averted were estimated based on data from Global Burden of Disease 2019, Malaria Indicator Survey 2018, and National Malaria Control Programme. Incremental cost-effectiveness ratios (ICERs) were estimated, and sensitivity analyses were used to test the robustness of the ICERs. Results The total financial cost of SMC implementation in Nampula province in 2023 was estimated to be $7,871,361.72. The study estimated a cost per targeted child of $6.05 and a cost per child who received full 3-day course of sulfadoxine-pyrimethamine in combination with amodiaquine (SPAQ) of $7.92. Furthermore, the cost per household with eligible children visited by a community distributor was $7.65; the cost per child who received day 1 SPAQ was $7.85 and the cost per child who received day 1 SPAQ by community distributor adhering to directly observed treatment was $8.50. In addition, the estimated cost was $93.50 per malaria case averted, $3286.59 per malaria death averted, and $130.16 per DALY averted. The ICERs were robust to a variety of alternative assumptions on costs and benefit estimates. Finally, $1,726,189.63 could have been saved if no ineligible children (60–119 months old) were treated through the programme. Conclusions In line with existing evidence from other African countries, SMC is found to be cost-effective in Mozambique. SMC is a beneficial prevention strategy to improve under-five health in the country, at a relatively low-cost.